FACTORS INFLUENCING THE FINANCIAL STABILITY OF ECONOMIC SUBJECTS - Mikhalenok, N.O; Berdnikova, L.F; Schneider, V.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
In the modern world, there are conditions when social responsibility and sustainable development become very practical and become a real factor of competitiveness on world markets. Russian companies do not stand aside.the most advanced of them, business leaders, show examples of this movement with their experience, partially or more fully integrating the goals and objectives of sustainable development into their strategies and action programs in the areas of corporate responsibility. Economic relations between participants in business processes are complex and unstable in modern realities. The complexity and instability of economic relations between business entities is caused not only by the influence of economic events, but also by political, social and environmental ones. All these factors of influence reduce the financial potential of a business entity, which determines the priority of issues of analysis and forecasting of the financial stability of the organization, as well as the development of its improvement. It should be noted that the problem of sustainable development can not be solved without appropriate information support that allows the company itself to assess the degree of achievement of the set financial and non-financial goals of long-term development, as well as to assess the effective or inefficient conduct of the company's business. The effectiveness of business processes is determined by the level of sustainable development of medium - and long-term functioning with the involvement of key stakeholders.